Pengaruh Leverage, CIR, dan IIR Terhadap ETR pada Perusahaan yang Terdaftar sebagai Saham LQ 45 Periode 2016-2019 dengan Profitabilitas sebagai Variabel Moderasi - Widia Irma Yunita; Atik Djajanti (Jurnal Riset Perbankan Manajemen dan Akuntansi, 2021)
This study examines the factors that affect the company's effective tax rate. Several factors are used, including Leverage, Capital Intensity Ratio, and Inventory Intensity Ratio with Profitability as a moderating variable. The purpose of this study is to empirically test whether Leverage, Capital Intensity Ratio, and Inventory Intensity Ratio with Profitability as a moderating variable affect the Effective Tax Rate of companies listed in the LQ45 stock category listed on the Indonesia Stock Exchange. The population used as the object of observation was 45 companies listed on the Indonesia Stock Exchange in the LQ45 category in the 2016 – 2019 period. The research sample was determined using the purposive sampling method and obtained a sample of 18 companies based on specific criteria. The analytical method used in this study is moderated regression analysis using SPSS 21 software. The results show that Inventory Intensity significantly affects the Effective Tax Rate. The results also show that Profitability moderates Leverage on the Effective Tax Rate, and Profitability moderates Inventory Intensity on the Effective Tax Rate. While Leverage and Capital Intensity Ratio does not significantly affect the Effective Tax Rate, this also shows that Profitability does not moderate the Capital Intensity Ratio on the Effective Tax Rate. In this study, there are still limitations. The influences of independent variables and moderating variables on the dependent variable can explain 30.4%, so it is necessary to add other independent and moderating variables to influence the Effective Tax Rate..